Pendidikan Karakter Pada Prodi Pendidikan Matematika Di Universitas KH. A. Wahab Hasbullah - Eliza Verdianingsih; Kholis Firmansyah (JoEMS (Journal of Education and Management Studies), 2019)
The purpose of this research is to describe character education in the Mathematics Education department at the University of KH. A. Wahab Hasbullah. This research is a qualitative research with the stages in this research are collecting problems, determining research objectives, concluding literature, collecting data, analyzing data, collecting conclusions / verification. The results of this research are the Department of Mathematics Education at the University of KH. A. Wahab Hasbullah has implemented character education in all academic activities that have been carried out in teaching and learning activities, student activities and community service activities